Technology adoption and diversity among Canadian business decision makers: Evidence from the survey of advanced technology - Rim Chatti; Marie Albertine Djuikom Tamtchouong; Manassé Drabo; Amélie Lafrance-Cooke (Economic and Social Reports, 2025)
The adoption of advanced technologies is a strategic imperative for companies that want to succeed in competitive markets by reducing costs, expanding their product range and increasing productivity. This study seeks to identify the factors that may explain the effect of characteristics specific to Canadian business decision-makers on technology adoption.